2011
DOI: 10.1258/phleb.2010.010041
|View full text |Cite
|
Sign up to set email alerts
|

Development of a device to determine the stiffness of elastic garments and bandages

Abstract: The reliability of this new method, which can be easily applied to not only elastic stockings but also elastic bandages, was verified. In clinical practice, the compression pressure should be selected in consideration of the prospective stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…5) Mannequin leg to assess stiffness Hirai and coworkers have developed a leg model whose circumference can be extended by one centimetre. 6) The increase of the pressure under a compression device on a specific leg point, e.g. at B1 corresponds to the stiffness of the material.…”
Section: Measurement Of Interface Pressure and Stiffness In Vivomentioning
confidence: 99%
“…5) Mannequin leg to assess stiffness Hirai and coworkers have developed a leg model whose circumference can be extended by one centimetre. 6) The increase of the pressure under a compression device on a specific leg point, e.g. at B1 corresponds to the stiffness of the material.…”
Section: Measurement Of Interface Pressure and Stiffness In Vivomentioning
confidence: 99%
“…13 The test results reveal that the pressures on the cylinders with the radius of 5 cm, are close to the expected range of pressures when these systems are used in clinical practice. However, further unpublished research of one of the group members revealed that if the method of enlargement described by Hirai et al 29,31 is used on cylinders, a diameter of 4 cm is closer to the expected range. 34 Based on these findings, the recommendation of the ICC working group is that for in vitro testing of compression bandages and bandage systems, cylinders should be used with a radius of 4 cm (circumference 25.1 cm).…”
Section: Radius/circumference Of the Cylindermentioning
confidence: 93%
“…The one leg model which has an application that is described as automatically (device 7), uses a manual winder to turn the fixed leg. 29 Although it is possible with this device to apply bandages with e.g. a 50% overlap, it is difficult to have the forces distributed evenly because of the irregularly shaped leg.…”
Section: Application Methodsmentioning
confidence: 99%
“…To determine the stiffness of the cloth studied, after their closed application without extra tension to the mannequin, the interface pressure under each cloth was continuously recorded by a pressure transducer (air-pack type analyser, Model AMI-3037, AMI Co., Tokyo, Japan), as described in a previous study. 13 The pack was placed on the medial area at level B1 of the leg mannequin, at the transition of the medial gastrocnemius muscle into the Achilles tendon in human legs, 11 and pressure recording while the gaiters or elastic stockings were applied was carried out continuously at intervals of 100 ms. During measurements, the circumference of the leg mannequin was increased to 1 cm by pushing the lever. An increase in the interface pressure was recorded as the stiffness (mmHg), as defined by the European Committee for Standardization (CEN).…”
Section: Methodsmentioning
confidence: 99%